2019
DOI: 10.1177/0734242x18823939
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic separation and recycling of anode and cathode materials from spent lithium iron phosphate batteries

Abstract: A novel approach to recycling of copper and aluminum fragments in the crushed products of spent lithium iron phosphate batteries was proposed to achieve their eco-friendly processing. The model of pneumatic separation that determines the optimal airflow velocity was established using aerodynamics. The influence of the airflow velocity, and the density and thickness, and their ratios, of the aluminum and copper fragments on pneumatic separation were evaluated. The results show that the optimal airflow velocitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Essential for a successful separation by screening and CES sorting was a crushing process which completely liberated the components of the battery cell, namely cathode foil, anode foils, separator foil and volatile solvents from the electrolyte. Previous studies (Bi et al, 2019a, 2019b) reported that the best heat treatment temperature and time are 300°C and 120 minutes, respectively. An in-depth investigation of the crushing and sieving results of the cathode slices of an LFP power battery is presented in Table 1 and Figure 6.…”
Section: Resultsmentioning
confidence: 98%
“…Essential for a successful separation by screening and CES sorting was a crushing process which completely liberated the components of the battery cell, namely cathode foil, anode foils, separator foil and volatile solvents from the electrolyte. Previous studies (Bi et al, 2019a, 2019b) reported that the best heat treatment temperature and time are 300°C and 120 minutes, respectively. An in-depth investigation of the crushing and sieving results of the cathode slices of an LFP power battery is presented in Table 1 and Figure 6.…”
Section: Resultsmentioning
confidence: 98%
“…Many other processes not discussed herein are summarized in Table S11 in Supplementary Information [224][225][226][227][228]…”
Section: Direct Recycling Approachmentioning
confidence: 99%
“…The topic of modeling the movement of particles in a stream of fluid is a crucial one in the context of the process of pneumatic transport, as well as the purification and separation of non-homogeneous mixtures [1,2]. These processes appear in many branches of industry, such as coal mining [3], environment and waste management [4], as well as agriculture and the food industry [5][6][7], with additional weight given to this problem by the huge quantity of materials involved. Such a model, if developed properly, may then be used to bolster these processes by predicting the behavior of the processed material during their course.…”
Section: Introductionmentioning
confidence: 99%
“…This allows them to be used as discriminatory traits for the separation of particles of similar sizes, which cannot be fully achieved by other means [8][9][10]. This method, known as pneumatic separation [4,5], is particularly important whenever significant differences in shape and mass, coupled with relatively similar particle sizes, occur between the desired material and the waste. This is commonly the case in the agriculture industry (e.g., grain versus chaff and shells), but also in the sortition of particulate biomass for the purposes of renewable energy production and waste management.…”
Section: Introductionmentioning
confidence: 99%